2014
DOI: 10.3390/molecules19079453
|View full text |Cite
|
Sign up to set email alerts
|

Blumea balsamifera—A Phytochemical and Pharmacological Review

Abstract: Abstract:The main components of sambong (Blumea balsamifera) are listed in this article. The whole plant and its crude extracts, as well as its isolated constituents, display numerous biological activities, such as antitumor, hepatoprotective, superoxide radical scavenging, antioxidant, antimicrobial and anti-inflammation, anti-plasmodial, anti-tyrosinase, platelet aggregation, enhancing percutaneous penetration, wound healing, anti-obesity, along with disease and insect resistant activities. Although many exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 31 publications
1
89
0
12
Order By: Relevance
“…Compare with habit, distribution, chromosome number, chemical composition and etc., we found the two main clades differ in habit, ecology, distribution, chromosome number and chemical composition, the Blumea DC. clade contains mostly perennial shrubs or subshrubs, and mostly distributed from evergreen forests, and also with the same chromosome number (2n = 18)and chromosome structure (6M+8m+4sm) (Lu, 1996), also the chemical composition are similar (Pang, Wang, Fan, Chen, Yu, Hu, Wang & Yuan, 2014). And clade II, which is a widespread paleotropical group that comprises mostly annual, weedy herbs of open forests and fields.…”
Section: Discussionmentioning
confidence: 99%
“…Compare with habit, distribution, chromosome number, chemical composition and etc., we found the two main clades differ in habit, ecology, distribution, chromosome number and chemical composition, the Blumea DC. clade contains mostly perennial shrubs or subshrubs, and mostly distributed from evergreen forests, and also with the same chromosome number (2n = 18)and chromosome structure (6M+8m+4sm) (Lu, 1996), also the chemical composition are similar (Pang, Wang, Fan, Chen, Yu, Hu, Wang & Yuan, 2014). And clade II, which is a widespread paleotropical group that comprises mostly annual, weedy herbs of open forests and fields.…”
Section: Discussionmentioning
confidence: 99%
“…The half maximal inhibitory concentration (IC50) of HGK for A549 cells was about 22 µM ( Figure 1B), while the IC50s of genkwanin and 3-methoxy genkwanin against A549 cells were >100 µM. A search of the literature has revealed that HGK that was isolated from the leaves of Blumea balsamifera DC displayed strong cytotoxicity against human lung cancer cells (NCI-H187) and a moderate toxicity against oral cavity cancer cells lines (KB) [19]. HGK induced DNA damage, cell cycle arrest, and cell apoptosis in glioma [20].…”
Section: Isolation and Identification Of Flavonoids From Genkwa Flosmentioning
confidence: 99%
“…Molecules 2019, 24, x FOR PEER REVIEW 3 of 12 leaves of Blumea balsamifera DC displayed strong cytotoxicity against human lung cancer cells (NCI-H187) and a moderate toxicity against oral cavity cancer cells lines (KB) [19]. HGK induced DNA damage, cell cycle arrest, and cell apoptosis in glioma [20].…”
Section: The Cytotoxic Effect Of Hgkmentioning
confidence: 99%
“…In China, it is called as Ai-Na-Xiang, whereas in Philippines it is called Sembung. B. balsamifera showed lots of biological effects on stomach, respiratory system [1], nervous system [2], and also showed sudorific [3], antifungal [4], anticancer [5,6], and antiobesity [4] effects.…”
Section: Introductionmentioning
confidence: 99%